Chinese librarianship in the digital era - Fang, Conghui (Chandos information professional series, 2013)
The library in China has been transformed by rapid socioeconomic development, and the proliferation of the Internet. The issues faced by Chinese libraries and librarians are those faced by library practitioners more globally, however, China also has its own unique set of issues in the digital era, including developmental imbalance between East and West, urban and rural areas, and availability of skilled practitioners. Chinese Librarianship in the Digital Era is the first book on Chinese libraries responding to these issues, and more. The first part of the book places discussion in historical context, before moving on to the digital environment of the Chinese library. The book then considers the issue of digital copyright in China, and debates the core values of the Chinese library. The next three chapters cover public and academic libraries, and library consortia. Finally, the book gives a view of the future prospects for libraries in China.